Qadhafi's Libya: Infinitely stable and reform-resistant? - Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2008)
When Libya's international isolation ended in 2004, Western leaders expressed their hope that political liberalization would follow. However, Qadhafi's repressive regime has so far turned out to be stable and resistant to reforms. Diplomatic normalization reduced the danger of regime change from outside and allowed Qadhafi to rebuild the sanction-hit oil industry. By doing so he was able to increase the resources available for redistribution, while on the other hand the country's structural, political and socioeconomic problems were swept under the carpet rather than resolved.This study examines the multiple challenges confronting the Libyan leadership today, and looks for the regime's strategies and instruments for providing solutions. The analysis of the state's reform capacities reveals the kind of Libya Europe can expect to be dealing within the medium term.Unless Libya's inefficient political structures can be reformed, the country's problems will remain unresolved. However, as long as Qadhafi remains in power, this is unlikely to happen, because the existing state of institutional and institutionalized chaos serves to maintain his grip on power. Power struggles among the elites also hamper coherent policymaking. These struggles are likely to intensify, bringing with them erratic political moves but no major destabilization - providing oil revenues hold up. With an eye to long-term reforms European leaders should open up as many communication channels as possible with the Libyan civil service and the universities. This may provide many Libyans with an insight into the way a democratic state functions and create a basis of mutual trust, which has been lacking due to the years of isolation and indoctrination
Keywords: 320